GE_GERICHTE C/19142/2015 vom 22. Dezember 2016 - GE Cour de justice (2016)
BAIL À LOYER ; AUTOMOBILE ; ASSURANCE RC DES VÉHICULES À MOTEUR ; AUTOMOBILE ; DOMMAGE ; CONDITION DE RECEVABILITÉ | CPC.311; LCR:58; CO.41;